Effectiveness of Job Training Programs In Improving The Competence Of Trainees at The Technical Implementation Unit of The Karawang Regency Manpower and Transmigration Office - Suci Aisyah Febriyanti; Suroso Suroso; Dwi Epty Hidayaty (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to determine the effectiveness of the job training program at the Karawang Manpower and Transmigration Office’s Vocational Training Center (BLK), specifically whether the program is effective in improving the competencies of trainees, as well as to identify the factors that support and hinder the implementation of the job training program. Methodology: The method used in this study is descriptive qualitative research with an evaluative case study approach. Data were collected through observation and documentation techniques, then analyzed using the Miles and Huberman (1994) model, which includes data reduction, data presentation, and drawing conclusions. Results: The findings of this study indicate that the vocational training program implemented by the Technical Implementation Unit of the Karawang Manpower Office’s Vocational Training Center (UPTD BLK) has been effective; however, there are still several aspects that require further evaluation, including upgrading training equipment to be more advanced similar to that used by companies, issuing BNSP certificates to trainees, and monitoring alumni who have secured employment. Findings: Based on interviews with training participants, the vocational training program organized by the Karawang Manpower Office’s Vocational Training Center (BLK Disnaker) has proven effective in enhancing participants’ competencies. However, there are still challenges, such as outdated training equipment therefore, the BLK Disnaker needs to update its training equipment to support the further development of the training process. Novelty: This study examines all aspects of effectiveness regarding learning materials, the learning process, training program outcomes, and the supporting and inhibiting factors of the training process. Originality: This study not only focuses on vocational training programs but also addresses training programs in general, the outcomes experienced by participants, and the supporting and inhibiting factors of training programs. Conclusion: Vocational training programs that utilize learning materials and systems for vocational training, in line with the Ministry of Manpower’s Training Program and supported by professional trainers in their respective fields as well as tools aligned with the foundational practices of each vocational field, are effective in enhancing trainees’ competencies. Type of Paper : Qualitative research article